2009
DOI: 10.1103/physrevd.80.064041
|View full text |Cite
|
Sign up to set email alerts
|

Self-dual black holes in loop quantum gravity: Theory and phenomenology

Abstract: In this paper we have recalled the semiclassical metric obtained from a classical analysis of the loop quantum black hole (LQBH). We show that the regular Reissner-Nordström-like metric is self-dual in the sense of T-duality: the form of the metric obtained in Loop quantum Gravity (LQG) is invariant under the exchange r → a0/r where a0 is proportional to the minimum area in LQG and r is the standard Schwarzschild radial coordinate at asymptotic infinity. Of particular interest, the symmetry imposes that if an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 76 publications
5
110
0
Order By: Relevance
“…The temperature and entropy of this kind of black hole are calculated by the use of the tunneling method. These first results presented in [38] replicate those found in the references [40][41][42], where other methods have been used. In this way, it can be demonstrated that the quantum tunneling formalism can be successfully applied to address the thermodynamics of LQBHs, opening a path for a whole range of applications.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…The temperature and entropy of this kind of black hole are calculated by the use of the tunneling method. These first results presented in [38] replicate those found in the references [40][41][42], where other methods have been used. In this way, it can be demonstrated that the quantum tunneling formalism can be successfully applied to address the thermodynamics of LQBHs, opening a path for a whole range of applications.…”
Section: Introductionsupporting
confidence: 80%
“…which coincides with the former Expression (11) found out in the references [40][41][42]. From the expression for LQBH temperature, one obtains for the entropy:…”
Section: Quantum Tunneling Radiation From Loop Quantum Black Holessupporting
confidence: 66%
See 2 more Smart Citations
“…In this way, a Loop Quantum Black Hole (LQBH), also called self-dual black hole, consists in a quantum corrected Schwarzschild black hole that appears from a simplified model of LQG by the use of semiclassical tools in the minisuperspace quantization approach [40][41][42][43].…”
Section: Loop Quantum Black Holesmentioning
confidence: 99%